The Reflection of Cognitive Level in Test Item Constructed by English Teacher in Summative Assessment - Nisrina, Nisrina (JUPE : Jurnal Pendidikan Mandala, 2023)
This study aimed to analyze the six levels of cognitive domain based on Revised Blooms Taxonomy and the use of HOTS and LOTS in the Final School Exam questions for twelfth-grade students, at teachers’ made test in summative assessment. This research was descriptive qualitative research that used content analysis as a method to analyze the specific character of each question. The researcher used Final School Exam questions from twelfth-grade students in the academic year 2021- 2022 at SMKN 8 Lhokseumawe as a data source and used a checklist table in collecting and analyzing data to find out the research results. The results of data analysis showed that the most dominant cognitive domain is the level of understanding (C2), which is 60% or 24 of 40 questions. The second highest is the level of Remembering (C1), which is 30% or 12 of 40 questions. Next is the Analyzing level (C4), which is 10% or 4 of 40 questions. The cognitive domain is classified into two levels, namely Lower Order Thinking Skill (LOTS) and Higher Order Thinking Skill (HOTS). Of the three categories applied to the test, it can be shown that 90% or 36 of the 40 questions are included in the LOTS category, while the other 10% or 4 of 40 questions are included in the HOTS questions. LOTS questions are much more dominant than HOTS questions.